2017
DOI: 10.13080/z-a.2017.104.027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wild oat plant density on spring wheat yield

Abstract: Wild oat (Avena fatua L.) is the most serious weed infesting cereal fields in Latvia. To predict possible yield loss at different wild oat densities field trials were established in four consecutive years, each year in a different spring wheat field in the southern part of Latvia. Growth dynamics and biomass of both crop and wild oat and grain yield were measured. Yield loss model developed by Cousens (1985) and exponential decay model were fitted to the data from each year. Grain yield and biomass of both spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…However, P. annua was characteristic only in conventional production in terms of frequency (48%) and average density (25 plants m -2 ) compared with organic production (11% and 1 plant m -2 ). The success of P. annua is in line with observations in the Nordic and Baltic countries (Tørresen et al 2006, Andreasen and Stryhn 2008, Nečajeva et al 2018) linked with moist soil conditions, adaptation to compact soil, successful overwintering and substantial phenotypic and genotypic variability (Warwick 1979). Increased area of reduced tillage in survey fields since the 1990s has likely favoured P. annua, as reported earlier in Norway (Tørresen et al 2003).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, P. annua was characteristic only in conventional production in terms of frequency (48%) and average density (25 plants m -2 ) compared with organic production (11% and 1 plant m -2 ). The success of P. annua is in line with observations in the Nordic and Baltic countries (Tørresen et al 2006, Andreasen and Stryhn 2008, Nečajeva et al 2018) linked with moist soil conditions, adaptation to compact soil, successful overwintering and substantial phenotypic and genotypic variability (Warwick 1979). Increased area of reduced tillage in survey fields since the 1990s has likely favoured P. annua, as reported earlier in Norway (Tørresen et al 2003).…”
Section: Discussionsupporting
confidence: 83%
“…In conventional production, the declining trend of E. repens biomass began in the late 1990s (Salonen et al 2013) as a consequence of common use of glyphosate, which has been the most sold herbicide in Finland for more than two decades (Tukes 2023). In comparison, a similar decline in E. repens was observed earlier in Denmark (Andreasen and Stryhn 2008) and Latvia (Nečajeva et al 2018), and also associated with increased use of glyphosate.…”
Section: Discussionsupporting
confidence: 76%
“…Wild oat causes 20–76% yield losses in wheat crop depending upon the severity and duration of infestation. Different studies have reported that wild oat severely hampers yield components of wheat crop in different regions of the world [ 11 , 21 – 24 ]. High temperature reduces seed viability and seed germination percentage of wild oat [ 25 ].…”
Section: Introductionmentioning
confidence: 99%